2020
DOI: 10.1016/j.cbi.2020.109125
|View full text |Cite
|
Sign up to set email alerts
|

Plants derived therapeutic strategies targeting chronic respiratory diseases: Chemical and immunological perspective

Abstract: The apparent predicament of the representative chemotherapy for managing respiratory distress calls for an obligatory deliberation for identifying the pharmaceuticals that effectively counter the contemporary intricacies associated with target disease. Multiple, complex regulatory pathways manifest chronic pulmonary disorders, which require chemotherapeutics that produce composite inhibitory effect. The cost effective natural product based molecules hold a high fervor to meet the prospects posed by current res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 133 publications
(127 reference statements)
0
11
0
1
Order By: Relevance
“…However, this issue may be addressed effectively by means of medicinal plant products. Medicinal plants possess the properties of having relatively lesser side effects and are cost effective in nature, due to which, they boast a potential advantage to address the challenges posed by the existing anticancer drugs (Prasher et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, this issue may be addressed effectively by means of medicinal plant products. Medicinal plants possess the properties of having relatively lesser side effects and are cost effective in nature, due to which, they boast a potential advantage to address the challenges posed by the existing anticancer drugs (Prasher et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have shown that flavonoids from traditional Chinese medicine (TCM) have certain protective effect on COPD [ 11 13 ]. Although there have been many research studies on flavonoids in treating COPD, the mechanisms of action of flavonoids are still not totally clear and few securable reviews illustrate the comprehensive and multiple pharmacological effects of flavonoids on COPD.…”
Section: Introductionmentioning
confidence: 99%
“…The application of novel drug delivery systems is gaining popularity for the treatment of various chronic lung diseases, including asthma (Mehta et al 2020a;Mehta et al 2020b;Prasher et al 2020). These include nanoparticle-based drug delivery, dry powder inhalers, micelle pharmacosomes, liposomes, dendrimers, and antibody-mediated drug delivery systems (Lanza et al 2017).…”
Section: Novel Drug Delivery Systemsmentioning
confidence: 99%